Bytelearn - cat image with glassesAI tutor

Welcome to Bytelearn!

Let’s check out your problem:

Rewrite the function by completing the square.

{:[f(x)=x^(2)+12 x+7],[f(x)=(x+◻)^(2)+◻]:}

Rewrite the function by completing the square.\newlinef(x)=x2+12x+7 f(x) = x^2 + 12x + 7 , f(x)=(x+)2+ f(x) = (x+\square)^2 + \square

Full solution

Q. Rewrite the function by completing the square.\newlinef(x)=x2+12x+7 f(x) = x^2 + 12x + 7 , f(x)=(x+)2+ f(x) = (x+\square)^2 + \square
  1. Given quadratic function: We start with the given quadratic function:\newlinef(x) = x2+12x+7x^2 + 12x + 7\newlineTo complete the square, we need to find a number to add and subtract to the function that will allow us to write it in the form of (x+a)2+b(x + a)^2 + b.
  2. Completing the square: First, we identify the coefficient of xx, which is 1212. To complete the square, we take half of this coefficient and square it. This gives us (122)2=62=36(\frac{12}{2})^2 = 6^2 = 36.
  3. Identifying the coefficient: We add and subtract this number 3636 inside the function to maintain the equality:\newlinef(x)=x2+12x+3636+7f(x) = x^2 + 12x + 36 - 36 + 7
  4. Adding and subtracting: Now we can rewrite the function by grouping the perfect square trinomial and the constants:\newlinef(x) = (x2+12x+36)36+7(x^2 + 12x + 36) - 36 + 7
  5. Rewriting the function: The perfect square trinomial (x2+12x+36)(x^2 + 12x + 36) can be factored into (x+6)2(x + 6)^2:\newlinef(x) = (x + 66)^22 - 3636 + 77
  6. Factoring the perfect square trinomial: Finally, we combine the constants 36-36 and +7+7 to simplify the function:\newlinef(x)=(x+6)229f(x) = (x + 6)^2 - 29

More problems from Solve a quadratic equation by completing the square